Bridging indoor and outdoor; an exploration of balconies in residential buildings - Lilja, Alice; Palmqvist, Ebba (My University, 2024)
The thesis aims to investigate the balcony and the related indoor spaces of the home, focusing on the relationship between indoor and outdoor spaces. The purpose is to explore the use of the balcony, what qualities the balcony provides and how the design can improve the living environment for the residents. The research questions investigate the functional, aesthetic and social qualities of private balconies in residential buildings and how the design of the interface between indoors and outdoors and the balcony can contribute to housing qualities. The methodological approach is divided into three main phases. The first phase focuses on finding a theoretical framework, focusing on housing qualities, balcony use and design. In the second phase an analysing tool is developed based on theory. The analysing tool is used to study qualities of several types of balconies. Selected built projects are analysed and surveys and interviews with residents are conducted. The final design proposal is presented in the third phase. Here, the theoretical framework and analysis made are combined to create a base that is used to develop two redesign proposals of balconies in an existing building with focus on the balcony and the related indoor spaces. The final design proposal is a redesign of a residential building in Kungsbacka in Sweden. The proposals aim to create housing qualities and to explore different kinds of experiences of balconies by redesigning the interface. The identified balcony qualities are categorised into four main categories: The border zone, Experience, Usage and Material and detail. The analyses reveal both common and varying qualities within balcony typologies, depending on specific projects and factors such as apartment design and surroundings. The thesis explores how balcony design influences the dwelling and the interaction between indoor and outdoor environments, focusing on aspects such as views, light, Keywords Balcony, private outdoor space, facade, housing qualities, dwelling privacy and social interaction. In conclusion, balconies are important for enhancing the physical and mental well-being of residents by providing access to nature, promoting social interaction and creating a sense of spaciousness.
Keywords: Balcony, private outdoor space, facade, housing qualities, dwelling